Teaching of pressure injury prevention and treatment using simulation - Alessandra Mazzo; Fernanda Berchelli Girão Miranda; Mateus Henrique Gonçalves Meska; Anaísa Bianchini; Rodrigo Magri Bernardes; Gérson Alves Pereira Junior (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To describe the construction of a high-fidelity clinical scenario simulation of "Pressure injury patient nursing care". Method: Report the experience of constructing a high-fidelity clinical scenario simulation based on the literature and on Bloom's taxonomy. Learning objectives, prior study material, fidelity, clinical case, necessary resources, problem solving, face and content validity, debriefing and evaluation were considered. Results: The scenario included cognitive, psychomotor and affective aspects; role-playing and the moulage technique were used, and it was positively evaluated by the students. Conclusion: The construction of planned, structured and validated simulated clinical scenarios brings learners closer to the clinical practice, allowing the development of the skills required for the prevention and treatment of pressure injuries. Implications for practice: Well-designed simulated clinical settings simulate nursing care training with fidelity to patients with pressure injury.